Pemanfaatan Artificial Intelligence dalam Aktivitas Dakwah Kontemporer: A Systematic Literature Review - Suci Ramadhani; Hasan Sazali; Elfi Yanti Ritonga (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2026)
This study aims to analyze the utilization of Artificial Intelligence (AI) in contemporary da’wah activities and to identify its opportunities, methodological transformations, and associated challenges. The research employs a qualitative approach using the Systematic Literature Review (SLR) method through the PRISMA procedure. The literature selection results indicate that 10 relevant scientific articles were reviewed in this study. The findings reveal that AI plays a significant role in enhancing the effectiveness of da’wah, particularly in expanding outreach, increasing interactivity, and enabling content personalization through technologies such as chatbots, digital applications, and social media platforms. Furthermore, AI drives a transformation in da’wah methods from conventional approaches to more adaptive and responsive digital practices. However, the study also identifies several challenges, including ethical issues, content validity, algorithmic bias, data security concerns, and the potential diminishing role of scholars (ulama) in guiding the community. Therefore, collaboration between preachers and technology developers, as well as strengthening digital literacy, is essential to ensure that AI utilization remains aligned with Islamic values.